A Case Report of Bronchial Asthma in a 56-Year-Old Mother With the Main Complaint of Shortness of Breath in the Emergency Room - Sahrun, Sahrun; Auliya, Khairani; Sulyastuty, Kadek (Jurnal EduHealth, 2024)
Asthma is a chronic disease that affects many children and adults in both developed and developing countries. According to WHO data, around 300 million people in the world have asthma, and it is estimated that this will continue to increase to reach 400 million in 2025. This research aims to explain the definition, etiopathology, clinical symptoms and signs, diagnosis, and appropriate, fast and accurate management of "Bronchial Asthma" so that correct treatment, good prognosis and patient safety are guaranteed. This type of research is a case study or a case report of a 56-year-old mother with bronchial asthma. A 56-year-old mother with Bronchial Asthma came consciously to the emergency room RSUD Gerung with complaints of shortness of breath. Shortness of breath has been felt since yesterday. The shortness of breath began with a cough had been experienced since 3 days of SMRS, which worsened yesterday. Phlegmy cough with phlegm that is difficult to expel. Now, the phlegm can start to be released little by little in a white color. Physical examination results: Consciousness (KU): Moderate, CM, BP: 110/70 mmHg, HR: 76 x/i, regular, RR: 36 x/i, T: 37oC, SpO2: 91-92% (room air). Head: Eyes: conjunctiva palpebra: anemic: (-/-), icteric: (-/-), pupil: isocoric, diameter: 3 mm, RCL +/+, RCTL +/+. Palpation: Strong cardiac impulse lift (+). Percussion: No apparent cardiac enlargement. Auscultation: HS I-II normal intensity, regular, murmur (-). Pulmo: Inspection: Expansion of the right chest = left, Palpation: Tactile fremitus in the left chest = right. Sonor percussion. Auscultation: Vesicular Ronchi +, Wheezing +. Auscultation: bowel sounds (+) normal. Chest X-ray Results In asthma, 75% of chest X-rays show a normal appearance. Findings that can be found in asthma patients include pulmonary hyperinflation. Thickening of the bronchial walls: peribronchial cuffing (nonspecific finding, but occurs in 48% of asthma cases). Pulmonary edema (rare), pulmonary edema due to asthma (typically seen in acute asthma attacks), cardiomegaly and bronchopneumonia.